Sunday

April 20, 2014

April 20, 2014

Posted by **nicky** on Tuesday, October 31, 2006 at 3:31pm.

3a-2(2a + 4)

you multiply the parenthesis by -2, giving you

3a -4a -8

combine like terms

-a-8

**Related Questions**

?? - 2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = ...

Math - In this problem: -2/a+2 + 3a/2a-1 First I made the denominators alike: -2...

Algebra - Remove the parentheses from the following expression, and combine like...

Math- factoring - Show all work and factor completely. 6a^2+5a-4 (6a^2+8a)-(3a-4...

algebra - 3(a+2)=4a I multiply 3*a+3*2=4a so 3a+6=4a I added 3a to 4a/ =7a and ...

Math - Simplify 2a^2 b^3 (4a^2 + 3ab -ab) A.) 8a^4 b^5 + 3a^3 b^5 - 2a^3 b^4 B...

alegbra - (2a+4b)-(3a-b)when and how do u know to change the signs? It might ...

algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...

math help - I need help factoring this out 6a^2-5a+1 okay so now after revising...

Math - Combine like terms a + a/4 + 3a/4 + 2a